2005
DOI: 10.1073/pnas.0502255102
|View full text |Cite
|
Sign up to set email alerts
|

Activated antigen-presenting cells select and present chemically modified peptides recognized by unique CD4 T cells

Abstract: CD4 T cells recognized posttranslationally modified peptides of the protein hen egg-white lysozyme (HEL), consisting of nitration of tyrosines and modifications of tryptophans in the T cell contact residues of the peptides. T cells were directed against modifications of a chemically dominant HEL peptide as well as a minor HEL peptide, bound to the class II histocompatibility molecule I-A k . The modified peptides were generated in vivo after immunization with native HEL molecules or were generated ex vivo by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 56 publications
4
30
0
2
Order By: Relevance
“…In the present study, we provide evidence that, as previously observed with CD4 T cells (23,25), CD8 T cells can specifically recognize epitopes containing a tyrosine-to-nitrotyrosine conversion. Y4 of gp33 has previously been shown to comprise an important TCR-contact point for T cells recognizing NY-gp33 in the context of H-2D b (27,29).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the present study, we provide evidence that, as previously observed with CD4 T cells (23,25), CD8 T cells can specifically recognize epitopes containing a tyrosine-to-nitrotyrosine conversion. Y4 of gp33 has previously been shown to comprise an important TCR-contact point for T cells recognizing NY-gp33 in the context of H-2D b (27,29).…”
Section: Discussionsupporting
confidence: 57%
“…These results imply that T cells bearing receptors capable of "recognizing" nitrated "self" peptides are not subject to the constraints of negative selection in the thymus (central tolerance) and that NYP formed during periods of inflammation may therefore constitute an important class of "neoautoantigens" that may play a role in inflammation and or autoimmune disease. Similar findings were recently reported for another MHC class II-restricted model Ag, hen egg lysozyme, that was treated to contain the oxidative modifications nitro-tryptophan or nitrotyrosine (25).…”
supporting
confidence: 72%
“…We recently called attention to nitration of tyrosine residues (13) and oxidation of tryptophans on peptides from the protein, hen egg-white lysozyme (HEL), bound to the class II histocompatibility molecule I-A k (14). These changes took place when APCs were activated during immunological reactions including infections.…”
mentioning
confidence: 99%
“…For example, antibodies against oxidized phospholipids have been detected in patients with cardiovascular diseases and diabetic nephropathy (9)(10)(11)(12). However, it is not known at present if nitration of tyrosine residues in proteins will induce immune responses in humans, despite studies in rabbits and mice indicating that several tyrosine nitrated proteins and peptides readily induce the generation of anti-nitrotyrosine antibodies (13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Clinical Relevancementioning
confidence: 99%